PENGARUH KARAKTERISTIK PEKERJAAN DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI KEPUASAN KERJA (Studi pada pegawai di kantor kelurahan Se kecamatan temanggung, kabupaten temanggung) - Muhammad Setyo Nusantoro, 11.52.02.0049 (Students Journal of Economic and Management, 2013)
Objectives of this research are to determine and to analyse the influence analysis of job carracteristic and organizasional culture on organizational commitment with job satisfaction as a mediating at kantor Kelurahan se Kecamatan Temanggung, Kabupaten Temanggung. Data are collecting by questionnaire technique from 121 employees at kantor Kelurahan se Kecamatan Temanggung, Kabupaten Temanggung. Respondents are sellected using purposive sampling technique. Technique examination of data used in this study cover validity test with factor analysis, test reliability with Alpha Cronbach, multiple regression analyse, test model, t â test and mediating test to prove the hypothesis of this research. The results of the analysis and discussion show that the job carracteristic and organizasional culture have significanly effect toward job satisfaction,Â job carracteristic, organizasional culture and job satisfaction also have a significant effect on organizational commitment, job satisfaction mediated the job carracteristic of organizational commitment and job satisfaction does not mediate the effect of organizasional culture the organizational commitment and the dominant factor affecting the organizational commitment is organizasional cultur. Keywords : Job Carracteristic, Organizational Culture, Job Satisfaction And Organizational Commitment